Equilibrium solubility, preferential solvation and solvent effect study of clotrimazole in several aqueous co-solvent solutions. (December 2020) - Li, Yanxun; Li, Congcong; Gao, Xiaoqiang; Lv, Hekun
Graphical abstract: Highlights: Clotrimazole solubility in four binary aqueous solutions was studied through experiment. Mole fraction solubility was correlated by Jouyban-Acree and van't Hoff-Jouyban-Acree models. Preferential solvation of clotrimazole in four aqueous solutions were studied via IKBIs method. Solvent effect on clotrimazole solubility was inspected by the KAT-LSER model. Abstract: The equilibrium solubility of clotrimazole in co-solvent mixtures of n -propanol/isopropanol/acetonitrile/1, 4-dioxane + water was attained by the saturation shake-flask technique at temperatures between 278.15 K and 323.15 K under ambient pressure of 101.2 kPa. The solubility of clotrimazole in mole fraction scale increased with increasing temperature and mass fractions of n -propanol/isopropanol/acetonitrile/1, 4-dioxane. The maximum value was recorded in the neat co-solvent for each mixture studied. The Jouyban-Acree model and van't Hoff-Jouyban-Acree model were applied to mathematically describe the dependence of clotrimazole solubility upon the co-solvent content and temperature, obtaining the values of relative average deviations and root-mean-square deviations no more than 8.02 × 10 −2 and 8.17 × 10 −4, individually. KAT-LSER model was implemented to quantitatively acquire evidence about solvent effect upon the variation of clotrimazole solubility magnitudes. The variation in clotrimazole solubility mainly depended upon the Hildebrand solubility parameter and dipolarity-polarizability of solutions in the four aqueous systems studied. Quantitative investigation was carried out for the local mole fractions of n -propanol/isopropanol/acetonitrile/1, 4-dioxane and water around solute clotrimazole by using the Inverse Kirkwood–Buff integrals way utilized to the solubility data determined. Clotrimazole was preferentially solvated by n -propanol/isopropanol/acetonitrile/1, 4-dioxane for these aqueous co-solvent mixtures in intermediate and n -propanol/isopropanol/acetonitrile/1, 4-dioxane-rich proportions.